The Role Of Green Accounting On Company Value - Ronald N Girsang; Tommy Ferdian; Laula Dwi Marthika; Eryasi Daryati (Nomico, 2025)
This study aims to analyze the effect of green accounting on the value of mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2023 period. The study population includes all mining companies on the IDX, with a sample of 16 companies that have complete annual reports and sustainability reports. A quantitative approach was used with the panel data regression analysis method and the Random Effect Model (REM) model, using EViews 13 software. Green accounting is measured using the PROPER rating, while company value is measured by Price to Book Value (PBV). The results show that green accounting has a positive and significant effect on company value. This finding supports the Signaling, Legitimacy, and Stakeholder theory, which states that good environmental performance is a positive signal for investors and strengthens the company's legitimacy in the eyes of the public.